On the dynamics and severity of bank runs: An experimental study - Schotter, Andrew; Yorulmazer, Tanju (Journal of Financial Intermediation, 2009)
This paper presents an experimental investigation of the factors that affect the dynamics and severity of bank runs. Our experiments demonstrate that the more information laboratory economic agents can expect to learn about the crisis as it develops, the more willing they are to restrain themselves from withdrawing their funds once a crisis occurs. Furthermore, our results indicate that the presence of insiders, who know the quality of the bank, significantly affects the dynamics of bank runs and helps mitigate their severity. We also show that deposit insurance, even of a limited type, can help diminish the severity of bank runs.